1996
DOI: 10.2307/3432807
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Painting in Biological Dosimetry: Assessment of the Ability to Score Stable Chromosome Aberrations Using Different Pairs of Paint Probes

Abstract: We exposed human peripheral lymphocytes in vitro to 0.3 and 1 Gy of 6OCo gamma rays to evaluate whether the ability and sensitivity to detect chromosomal aberrations by chromosome painting is independent or not to the specific paint probes. To detect structural aberrations (translocations), we painted chromosome spreads simultaneously with two whole-chromosome libraries for chromosomes 1, 2, 3, 4, 5, 6, 7, 11, 13, 16, and 18. To compare the rate of chromosome translocations detected by the different pairs of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Gamma rays directly induced the CA in human lymphocytes (Brandriff et al 1988, Lefrancois et al 1989, Lijima and Morimoto 1991, Milkovic-Kraus et al 1992, Huber et al 1992, Kosaka et al . 1995, Sing et al 1995, Kasai et al 1996, Chambrette et al 1996, Garcia-Sagredo et al 1996, in human chorionic villi (Salvi et al 1993), in Macaca mulatta lymphocytes (Guedeney et al 1988), in cynomolgus peripheral lymphocytes (Guedeney et al 1989), in rhesus monkey (Van Buul 1989) and in mouse (Sjoblom et al 1995, Zang 1995. It is shown that gamma rays directly and indicrectly affected the DNA and caused to chromosome mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma rays directly induced the CA in human lymphocytes (Brandriff et al 1988, Lefrancois et al 1989, Lijima and Morimoto 1991, Milkovic-Kraus et al 1992, Huber et al 1992, Kosaka et al . 1995, Sing et al 1995, Kasai et al 1996, Chambrette et al 1996, Garcia-Sagredo et al 1996, in human chorionic villi (Salvi et al 1993), in Macaca mulatta lymphocytes (Guedeney et al 1988), in cynomolgus peripheral lymphocytes (Guedeney et al 1989), in rhesus monkey (Van Buul 1989) and in mouse (Sjoblom et al 1995, Zang 1995. It is shown that gamma rays directly and indicrectly affected the DNA and caused to chromosome mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the dose was estimated either by measuring the TL in entire genome using GTG banding 15 or FISH with a few painted chromosomes 16,17 . The concern in the TL scoring with FISH is that, extrapolation of genomic TL with a few painted chromosomes to the entire genome is based on assumptions 9 , though literature shows evidence that radiation-induced TL are distributed randomly 36 as well as non-randomly 37 . Hence, the TL frequency was examined in the PBL exposed in vitro to g-radiation, through WCP with two chromosomes, GTG banding as well as m-FISH to validate FISH with selective painting of a few chromosomes for biological dosimetry.…”
Section: Fluorescence In Situ Hybridisation (Fish) To Quantify Cumulamentioning
confidence: 99%